2019
DOI: 10.5194/angeo-2019-120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of local gravity wave forcing in the lower stratosphere on the polar vortex stability: Effect of longitudinal displacement

Abstract: Abstract. The effects of gravity wave (GW) breaking hotspots in the lower stratosphere, especially the role of their longitudinal distribution, are evaluated through a sensitivity study by using a simplified middle atmosphere circulation model. For the position of the local GW hotspot, we first selected a fixed latitude range between 37.5 and 62.5° N and a longitude range from 112.5 to 168.75° E, as well as an altitude range between 18 and 30 km. This confined GW hotspot was then shifted in longitude by 45° st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…For the RM hotspot, a suppressed upward propagation of resolved waves throughout the stratosphere leads to significant positive EPFD anomalies, but only near the stratopause (and continuing to the mesosphere, see Figures ). The diversity of the resolved wave anomalies in the stratosphere dependent on the hotspot is in agreement with mechanistic model studies with artificial OGWD enhancements (see Šácha et al., 2016 for the EA hotspot and Samtleben et al., 2019, 2020 also for different regions). This indicates that the anomalous resolved wave propagation starting from the lower stratosphere is directly caused by the strong OGWD events and not by the “hotspot preconditioning”.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…For the RM hotspot, a suppressed upward propagation of resolved waves throughout the stratosphere leads to significant positive EPFD anomalies, but only near the stratopause (and continuing to the mesosphere, see Figures ). The diversity of the resolved wave anomalies in the stratosphere dependent on the hotspot is in agreement with mechanistic model studies with artificial OGWD enhancements (see Šácha et al., 2016 for the EA hotspot and Samtleben et al., 2019, 2020 also for different regions). This indicates that the anomalous resolved wave propagation starting from the lower stratosphere is directly caused by the strong OGWD events and not by the “hotspot preconditioning”.…”
Section: Resultssupporting
confidence: 87%
“…Samtleben et al. (2020) have shown that the OGWD influence on the zonal mean dynamics is mainly driven by changes in the propagation of planetary‐scale RWs with zonal wavenumber 1 (PW1). Decomposition of the EPF and EPFD anomalies according to the wavenumber (Figures 1d–1l) shows that the propagation of PW1 is suppressed for all three hotspots.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations